White oat leaf diseases control and production damages in response to the rate and number of fungicide applications (Revista de Ciências Agroveterinárias, 2008)
The leaf rust and helmintosporiosis are leave diseases that affect white oat grain yield and components. This research was carried out aiming to quantify the injuries caused by these diseases, considering a multiple pathosystem, to grain yield, 1,000 grains mass and hectoliter weight, and to determine these diseases control percentage in response to the number (one, two and four) and rate (½, ¾ and indicated rate) of piraclostrobina + epoxiconazole fungicide application. Two white oat cultivars were tested: UPFA 20 Teixeirinha and UPFA 22 Temprana. The experiment was set in two growing seasons: 2006, under crop rotation, and 2007, under monoculture. Ten treatments were assessed on each year, distributed randomly in blocks with four replications. For both cultivars, the disease intensity was quantified in phenological stages ranging from the start of tillering to hard dough. The leaf incidence and severity data were submitted to the area under the disease progress curve (AUDPC). Helminthosporium was the predominant disease until flowering for both growing seasons and cultivars. Leaf rust intensity increased in the subsequent stages. Grain yield, 1,000 grain mass and hectoliter weight damages were higher in 2007 than in 2006 for both cultivars, with percentages varying, respectively, from 5.46% to 50.30%, 3.56% to 32.72 %, 1.49% to 7.20% for UPFA 20, and from 11.10% to 48.45%, 2.08% to 26.01%, 1.88% to 11.51% for UPFA 22. Comparing the AUDPC values, there were greater disease intensities in 2007, possibly due the monoculture system. The AUDPC values showed that UPFA 20 was more susceptible to leaf diseases than UPFA 22, even though it showed higher values for grain yield. The control percentage of leaf diseases was higher in 2007 for both cultivars, reaching, based on the leaf severity, 86.74% and 85.90% for UPFA 20 and UPFA22, respectively. The highest chemical economic return for both cultivars was achieved with two applications of fungicide indicated rate in 2006, and with four applications in 2007.
Keywords: Avenna sativa; chemical control; Puccinia coronata; Drechslera avenae.